A Case of Femoral Arteriovenous Fistula Causing High-Output Cardiac Failure, Originally Misdiagnosed as Chronic Fatigue Syndrome. (20th May 2014) - Porter, J.; Al-Jarrah, Q.; Richardson, S.
Abstract : Percutaneous arterial catheterisation is commonly undertaken for a range of diagnostic and interventional procedures. Iatrogenic femoral arteriovenous fistulas are an uncommon complication of these procedures. Most are asymptomatic and close spontaneously, but can rarely increase in size leading to the development of symptoms. We report a case of an iatrogenic femoral arteriovenous fistula, causing worsening congestive cardiac failure, in a 34-year-old marathon runner. This was originally diagnosed as chronic fatigue syndrome. Following clinical examination, duplex ultrasound, and CT angiography a significant arteriovenous fistula was confirmed. Elective open surgery was performed, leading to a dramatic and rapid improvement in symptoms. Femoral arteriovenous fistulas have the potential to cause significant haemodynamic effects and can present many years after the initial procedure. Conservative, endovascular, and open surgical management strategies are available.